0759 A real world study assessing patient satisfaction in the primary care setting in relation to excessive daytime sleepiness in participants with obstructive sleep apnea. (25th May 2022) - Parthasarathy, Sairam; Hyman, Danielle; Doherty, James; Saad, Ragy; Zhang, Jerry; Morris, Susan; Eldemir, Lev; Fox, Benjamin; Vang, Mai Ka Ying; Schroeder, Jessica; Marshall, Nell; Parks, Gregory
Abstract: Introduction: Excessive daytime sleepiness (EDS) is common in obstructive sleep apnea (OSA), despite positive airway pressure (PAP) therapy. These analyses evaluated EDS prevalence and its relationship with satisfaction with care in participants with OSA receiving OSA care in a primary care setting. Methods: US residents (aged ≥18 years, self-reported physician OSA diagnosis [1/1/2015–3/31/2020]) completed a survey in Evidation Health's Achievement app assessing Epworth Sleepiness Scale (ESS), specialties of healthcare providers (HCPs) treating OSA, PAP usage, and satisfaction with HCPs and overall OSA care. Self-reported PAP use was categorized: nonuse, nonadherent (<4 h/night, <5 d/wk), intermediate (4–6 h/night, ≥5 d/wk), or highly-adherent (≥6 h/night, ≥5 d/wk) (PAP-adherent=intermediate+highly-adherent groups). Linear modeling assessed the relationship between PAP use and ESS score; logistic regression assessed impacts of PAP adherence and EDS on satisfaction with care. P-values are uncontrolled for multiplicity. Results: Participants (N=2289) were 50.3% female; 82.5% White; 44.8±11.1 years old (mean±SD); with BMI 35.4±8.7 kg/m2; 42.5% had EDS (ESS>10). OSA was primarily managed by sleep specialists (43.5%), general practitioners (GPs) (42.5% [28.9% saw a GP only; 13.6% saw a GP and a specialist/pulmonologist]), and/or pulmonologists (18.0%). Among participants with OSA managed by a GP only (n=662), proportions (95% CI) with EDS were: PAP nonuse (49% [42.8–54.9]), nonadherent (47% [31.5–63.2]), intermediate (47% [33.4–60.8]), and highly-adherent (35% [29.3–39.9]). Linear modeling (PAP users; n=398) showed an additional h/night of PAP use was associated with lower ESS scores (estimate [SE], –0.26 [0.13]; P<0.05); logistic regression showed association between PAP adherence and higher satisfaction with HCPs (adjOR=2.26; 95% CI=1.09–4.70; P<0.05) and OSA care (adjOR=1.58; 95% CI=0.75–3.36; P>0.05). There was an association between presence of EDS and lower satisfaction with their HCPs (adjOR=0.62; 95% CI=0.39–0.99; P<0.05) and OSA care (adjOR=0.49; 95% CI=0.31–0.79; P<0.05). Conclusion: In a real-world population of participants with OSA receiving OSA care from GPs, EDS was common, even among highly-adherent PAP users. ESS scores were generally lower with increasing PAP adherence. PAP adherence was associated with increased satisfaction with their HCPs; EDS was associated with lower satisfaction with HCPs and overall OSA care. Support (If Any): Jazz Pharmaceuticals